2000
DOI: 10.1086/313930
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter cinaedi Septic Arthritis and Bacteremia in an Immunocompetent Patient

Abstract: We report on the first case of documented Helicobacter cinaedi septic arthritis in an immunocompetent heterosexual young man. The patient presented no identified risk factor except for contact with animals that have been incriminated as a possible source of infection, particularly for these patients. Despite prolonged bacteremia, the response to long-term therapy with ciprofloxacin and rifampin was excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 11 publications
(8 reference statements)
0
49
0
2
Order By: Relevance
“…With regard to erythromycin and ciprofloxacin, Kiehlbauch et al (11) have shown that H. cinaedi isolates from both humans and animals are susceptible to both of these antimicrobial agents, with MIC ranges for erythromycin and ciprofloxacin in animal-isolated H. cinaedi of Ͻ0.06 to 0.5 mg/liter and 0.12 to 1.0 mg/liter, respectively, and 0.06 to Ͼ128 mg/liter and 0.12 to 8.0 mg/liter in isolates from humans, respectively. Ciprofloxacin was also reported to successfully eradicate H. cinaedi infections in humans in 1991 and 2000 (15,23). These results suggest that H. cinaedi was once susceptible to macrolides and fluoroquinolones, with the majority of H. cinaedi isolates gaining resistance in response to the increased use of these antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to erythromycin and ciprofloxacin, Kiehlbauch et al (11) have shown that H. cinaedi isolates from both humans and animals are susceptible to both of these antimicrobial agents, with MIC ranges for erythromycin and ciprofloxacin in animal-isolated H. cinaedi of Ͻ0.06 to 0.5 mg/liter and 0.12 to 1.0 mg/liter, respectively, and 0.06 to Ͼ128 mg/liter and 0.12 to 8.0 mg/liter in isolates from humans, respectively. Ciprofloxacin was also reported to successfully eradicate H. cinaedi infections in humans in 1991 and 2000 (15,23). These results suggest that H. cinaedi was once susceptible to macrolides and fluoroquinolones, with the majority of H. cinaedi isolates gaining resistance in response to the increased use of these antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…The first H. cinaedi infection in humans was reported in 1984, after isolation from a homosexual man (32). Since then, H. cinaedi infections have usually been detected in immunocompromised patients (1,12,13,15,16,20,31), although in some cases, they may also occur in patients with normal immunity (9,33). The clinical manifestations of H. cinaedi include enteritis, proctocolitis, cellulitis, arthritis, and bacteremia.…”
mentioning
confidence: 99%
“…Other Helicobacter species, such as H. cinaedi and H. fennelliae, have been occasionally recovered from the blood of adult patients, mostly patients with human immunodeficiency virus (HIV) infection who presented with cellulitis (7,13,19,24). One recent investigation isolated H. cinaedi from an immunocompetent patient with septic arthritis and bacteremia (10). In the present report, we describe the first immunocompetent adult with recurrent Helicobacter sp.…”
mentioning
confidence: 66%
“…Early reports described its association with proctocolitis, but H. cinaedi may also cause bacteremia (3,17,19,22,26,35), cellulitis (2, 13), and septic arthritis (2,14). Infection is sometimes asymptomatic (15,16,25) and can occur in other immunocompromised patients (13) or occasionally in normal hosts (14,30,32).Like Campylobacter infections, enterohepatic Helicobacter infections are believed to be acquired by humans from pets or farm animals (28). In one series of 23 patients with H. cinaedi infections (13), the most frequent exposures of interest were contact with animals (n ϭ 9) or untreated surface water (n ϭ 3), However, little is known about the animal reservoir(s) for H. cinaedi.…”
mentioning
confidence: 99%
“…H. cinaedi is most commonly isolated from homosexual men infected with human immunodeficiency virus. Early reports described its association with proctocolitis, but H. cinaedi may also cause bacteremia (3,17,19,22,26,35), cellulitis (2,13), and septic arthritis (2,14). Infection is sometimes asymptomatic (15,16,25) and can occur in other immunocompromised patients (13) or occasionally in normal hosts (14,30,32).…”
mentioning
confidence: 99%